2014
DOI: 10.1155/2014/381983
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Determination of Pollen Count Using Google Search Queries for Patients Suffering from Allergic Rhinitis

Abstract: Background. The transregional increase in pollen-associated allergies and their diversity have been scientifically proven. However, patchy pollen count measurement in many regions is a worldwide problem with few exceptions. Methods. This paper used data gathered from pollen count stations in Germany, Google queries using relevant allergological/biological keywords, and patient data from three German study centres collected in a prospective, double-blind, randomised, placebo-controlled, multicentre immunothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
0
17
0
2
Order By: Relevance
“…The analysis of online searches, in particular using Google trends, has shown potential in predicting changes in flu infections (42) and in other areas of medicine (38). Nevertheless, this type of big data analysis is just beginning (38) and more research is needed to prove its value in predicting the onset of allergic rhinitis symptoms due to the pollen season (43). Moreover, the onset of the pollen season cannot be predicted using these models.…”
Section: Time Of Onset Of the Allergy Seasonmentioning
confidence: 99%
“…The analysis of online searches, in particular using Google trends, has shown potential in predicting changes in flu infections (42) and in other areas of medicine (38). Nevertheless, this type of big data analysis is just beginning (38) and more research is needed to prove its value in predicting the onset of allergic rhinitis symptoms due to the pollen season (43). Moreover, the onset of the pollen season cannot be predicted using these models.…”
Section: Time Of Onset Of the Allergy Seasonmentioning
confidence: 99%
“…Google Trends (GT) is a web-based surveillance tool that uses aggregated Google searches to summarise the searching trends of specific queries. Recent studies have suggested the utility of GT for assessing the seasonality of allergic diseases [12-17] and for detecting influenza epidemics [18]. GT data may closely reflect the real-world epidemiology of allergic rhinitis (AR) and could potentially be used as a monitoring tool for AR [19].…”
Section: Introductionmentioning
confidence: 99%
“…Este resultado coincide con recientes publicaciones en otras partes del mundo (13,14) . Se puede deducir que el máximo en las búsquedas coincide con el periodo en que se intensifican los síntomas de la polinosis de Olea, ya que coinciden con el pico polínico de Córdoba.…”
Section: Resultados Y Discusiónunclassified